Synthesis and Characterization of Some Transitional Metal Complexes of New Polydentate Ligands Containing 1,8-Naphthyridine Moiety - Swamy, S.J.; Raveender Reddy, S.; Dharma Reddy, A.; Bhaskar, K. (Asian Journal of Chemistry, 2011)
The substituted 1,8-naphthyridines, 2-hydroxy-1,8-naphthyridine-3-carboxylic acid hydrazide (HNch) and 2-hydroxy-1,8-naphthyridine-3-carboxylic acid o-hydroxybenzylidene hydrazide (HNCHBh) react with Ni(II), Cu(II) and Zn(II) acetate to yield complexes of definite composition. The complexes have been characterized by elemental analysis, thermal, conductance, magnetic studies and IR, electronic, NMR and ESR spectral data. The HNCh and HNCHBh form the complexes of formula [M(HNCh)2] and [M(HNCHBh) (H2O)2], respectively.